TINJAUAN PROSES PELAPORAN EKSTERNAL UNIT REKAM MEDIS DI RSU SUAKA INSAN BANJARMASIN TRIWULAN 1 TAHUN 2022 - Syahida Hayati; Eka Rahma Ningsih (JEMPOL : Jurnal Elektronik Mahasiswa Polanka, 2023)
Based on the results of a preliminary study at RSU Asylum in San Banjarmasin In making hospital external reporting, it was found that there were obstacles, one of which was that the officers mistakenly entered data, so that the reported data still contained some errors. The purpose of this study was to find out the external reporting process of the medical record unit in RSU Asylum insan Banjarmasin, Type of research with descriptive research methods with a qualitative approach. How to collect data using observation and interview methods. The results showed that the types of reports were RL 1 basic hospital data, RL 4 patient morbidity and mortality data, and RL 5 monthly data. Sources of data from the emergency room, ward, census from SIMRS. The external reporting process is done manually by taking data in each unit and computerized data is available at SIRS Online. The conclusions of the results of this study include the types of reports used according to SIRS Online, data sources (RL 1 from basic hospital data, RL 4 from wards and RL 5 from census reports, SIMRS, and medical history), and the reporting process using manual and computerized